Effects of Terminal Motif on the Self-Assembly of Dexamethasone Derivatives - Liu, Hui; Yu, Ailing; Dai, Mali; Lin, Dan; Lin, Deqing; Xu, Xu; Li, Xingyi; Wang, Yuqin (Frontiers in Chemistry, 2020)
Tailoring the terminal motif of molecules including drugs might be significantly affect their self-assembly tendency in aqueous solution, thus providing a rational strategy to modulate its macroscopic characteristics of supramolecular assembly. A model drug of dexamethasone (Dex) was esterified by different fatty acids (succinic acid, SA; glutaric acid, GA and adipic acid, AA) and aromatic acid (phthalic acid, PA) to generate a series of Dex derivatives. Aqueous solution of Dex-SA, Dex-GA and Dex-AA turned into hydrogel spontaneously after a period time of incubation (24, 48 and 72h, respectively) via the auto-hydrolytic strategy, while aqueous solution of Dex-PA did not result in the hydrogelation during 3 days incubation. Aqueous solutions of Dex-SA, Dex-GA and Dex-AA underwent apparent hydrolysis (10.73±0.64%, 15.17±2.24% and 17.29±1.39%, respectively), while Dex-PA exhibited a minimal hydrolysis (less than 1%) in a period of 28 days study, as indicated by in vitro hydrolytic test. Morphological observation showed that the hydrogel formed by Dex-SA was composed of uniform nanofibers, while hydrogels formed by Dex-GA and Dex-AA were derived from irregular particles. The mechanical strength of hydrogel formed by Dex-SA was much bigger than that of hydrogels formed by Dex-GA and Dex-AA, as indicated by rheological test. Moreover, the acylation of Dex did not compromise its potent anti-inflammatory activity in a lipopolysaccharide (LPS)-actived RAW 264.7 macrophage.